Cross Generational Relationships and Cinema
XVI, 260 p. 20 illus. in color.
Keywords: Depictions of cross generational relationships have always been present in popular cinema. While such relationships have historically operated within the framework of heteronormativity, and have usually explored cross generational romance in the context of older men/younger women, contemporary depictions have expanded to focus also on taboo configurations of love between older women and younger men and cross generational LGBT coupledom. Contemporary depictions have sought to complicate not only heteronormativity in cross generational relationships, but also to navigate the differences between socially acceptable love and transgressive desire. This collection focuses on the changing values and attitudes of cross generational relationships and addresses the often divisive relationship between the discourses of youth and ageing in popular culture.